The Influence of Social Media Marketing and Electronic Word of Mouth on Purchase Intention Through Brand Image as Intervening Variables: A Study on Azarine Cosmetic in Malang City - Rifki Warri Zain; Irmayanti Hasan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
TikTok has emerged as the most popular social media app among today's Generation Z users. Simultaneously, this presents a new challenge for businesses, particularly in the intensely competitive local beauty product market as well as worldwide. Azarine Cosmetics is one of the cosmetic brands being investigated. The purpose of this study is to investigate how brand image and social media marketing affect consumers' intentions to make purchases. 155 members of Malang City's Generation Z were given a questionnaire as part of the study's quantitative methodology. Purposive and nonprobability sampling methods were used in the sampling process. The Partial Least Squares Structural Equation Modeling (PLS-SEM) approach was used to analyze the data. Three factors social media marketing, Ewom, and brand image have a significant impact on purchase intention, according to the research findings. Regarding the connection between Ewom and social media marketing, both significantly and favorably affect the perception of a brand. Social media marketing and electronic word-of-mouth, however, are not able to strongly affect purchase intention through brand image. This study broadens our knowledge of the factors influencing consumers' intentions to make purchases in the digital age. Further research efforts might be based on the findings of this study.